Biplanar Proximal Tibial Opening-Wedge Osteotomy for a Chronic PCL Tear With Medial Compartment Arthritis - Mark T. Banovetz BS; Jacob A. Braaten BA; Morgan D. Homan DO; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2023)
Background: Chronic posterior cruciate ligament (PCL) insufficiency leads to instability of the knee, resulting in increased loading of the medial and patellofemoral compartments. Chronic PCL insufficiency progressively damages the menisci and chondral surfaces and can accentuate and worsen varus malalignment. Biplanar proximal tibial opening-wedge osteotomy (BPTO) is a treatment option for chronic PCL tears with medial compartment arthritis which concurrently treats sagittal (flat slope) and varus coronal alignment. Indications: Opening-wedge BPTO is indicated in active patients who present with varus malalignment and flat slope with concomitant degenerative medial compartment osteoarthritis and PCL insufficiency. In general, BPTO is contraindicated in patients with a significantly elevated body mass index (BMI), smokers, or in those who have advanced tricompartmental osteoarthritis. Technique Description: Preoperative long-leg radiographs are essential to preoperative evaluation. Ideal coronal alignment following correction would have the mechanical axis pass through the apex of the lateral tibial eminence to properly off-load the medial compartment. Magnetic resonance imaging (MRI) studies are also useful for determining the presence and extent of concomitant soft tissue and chondral injury, especially in the lateral compartment. This video demonstrates the senior author's preferred technique for a biplanar proximal tibial opening (PTO) with concomitant chondroplasty and partial medial meniscectomy (PMM). The senior author's preferred order of operations is also displayed and involves first performing an arthroscopy, then proceeding with the open portions of the case, including the medial approach and subsequent osteotomy. Results: Past studies have supported PTO as a reliable treatment option for varus malalignment. Bode et al reported a 5-year survival rate of 96% of patients with an overall complication rate of 8.6%. The authors also reported that Lysholm scores were also significantly improved at 60-month follow-up compared with preoperative scores. Discussion: This is a technique for the correction of a varus malalignment with concomitant flat slope and PCL insufficiency with biplanar open-wedge PTO. This operation corrects the mechanical axis and sagittal slope of the knee and restores proper load distribution across the tibiofemoral articulation. In conclusion, a biplanar open-wedge PTO is a useful alternative to joint arthroplasty for active patients with a chronic PCL tear, medial compartment arthritis, and varus malalignment. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.